2013
DOI: 10.1007/s00442-013-2678-8
|View full text |Cite
|
Sign up to set email alerts
|

Can synchronizing feather-based measures of corticosterone and stable isotopes help us better understand habitat–physiology relationships?

Abstract: Physiological mechanisms link the environment with population dynamics, and glucocorticoid hormones are of particular interest because they respond adaptively to environmental change and can influence vertebrate reproduction and fitness. We tested a novel approach of synchronizing feather-based measures of corticosterone (the primary avian glucocorticoid; CORTf) and ratios of stable isotopes (SIs) of C (δ(13)C) and N (δ(15)N) to provide information about environmental conditions and an integrated physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…Nonetheless, immunoassays including white blood cells proliferation and macrophage burst and phagocytic activity can be used either in macro-invertebrates (Galloway and Depledge, 2001) or fish (Zelikoff et al, 2000), and also help disentangle stress from immune responses. The stress-fitness relationship is a pivotal topic in ecology but such relationship is still far from being clear (Fairhurst et al, 2013;Wikelski and Cooke, 2006). Fitness has been positively and negatively related to stress measures in several wild species but as far as we are aware, none of them have focused on wild free-living fish or macroinvertebrates of European Mediterranean rivers.…”
Section: Stress Responsesmentioning
confidence: 99%
“…Nonetheless, immunoassays including white blood cells proliferation and macrophage burst and phagocytic activity can be used either in macro-invertebrates (Galloway and Depledge, 2001) or fish (Zelikoff et al, 2000), and also help disentangle stress from immune responses. The stress-fitness relationship is a pivotal topic in ecology but such relationship is still far from being clear (Fairhurst et al, 2013;Wikelski and Cooke, 2006). Fitness has been positively and negatively related to stress measures in several wild species but as far as we are aware, none of them have focused on wild free-living fish or macroinvertebrates of European Mediterranean rivers.…”
Section: Stress Responsesmentioning
confidence: 99%
“…Work with birds has shown that feathers contain corticosterone (CORT) (Bortolotti et al, 2008;Koren et al, 2012), the primary avian GC. CORT in feathers (CORT f ) has been correlated with variation in parental provisioning (Fairhurst et al, 2012b), nest box microclimate (Fairhurst et al, 2012a), environmental enrichment (Fairhurst et al, 2011), expression of carotenoid-based signals (Bortolotti et al, 2009b;Mougeot et al, 2010;Kennedy et al, 2013), egg mass (Kouwenberg et al, 2013), stable isotopes of carbon (Fairhurst et al, 2013) and components of fitness (Bortolotti et al, 2008;Koren et al, 2012). This biomarker relates to diverse ecological factors, suggesting that it integrates CORT secretion in general, rather than expresses a response to any specific source of environmental variation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used as a tool to associate physiology with feather coloration, feather quality, and social signals (Bortolotti et al, 2009b;Lattin et al, 2011;Kennedy et al, 2012;Martínez-Padilla et al, 2013). It has also been applied to assess health condition (Harms et al, 2010;Koren et al, 2012) and to comprehend relationships between habitat and animal physiology (Fairhurst et al, 2011(Fairhurst et al, , 2013, among other applications. Nonetheless, research in the possibilities and potential offered by this matrix is still in its beginnings, with important gaps hindering proper interpretation (Hõrak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%